Perjuangan Ibu dalam Memberikan Stimulasi Tumbuh Kembang pada Anak yang Pernah Terinfeksi Cytomegalovirus - Noor Yunida Triana (Viva Medika, 2019)
A child that ever infected Cytomegalovirus (CMV) may experience disability and delayed growth and development. The study aim to obtain an overview of the mother’s struggle in providing growth stimulation in children who have been infected with CMV. The research method was descriptive qualitative with a phenomenological approach through semi-structured interviews with seven mothers. This study identified four themes: being a caregiver, treatment efforts, provide stimulation of growth and development by optimum and efforts to provide training at the therapy site. The results of this study on nursing care is nurses can initiate the formation of peer group to support and assist the struggles of the mothers who have children who have been infected with CMV.